Aru Shah and the nectar of immortality - Chokshi, Roshani (Chokshi, Roshani. Pandava novel ;bk. 5., 2022)
The Pandavas call on old friends, make new allies, and face fearsome trials as they embark on a mission to stop the Sleeper from accessing the nectar of immortality, but ultimately Aru must decide who deserves immortality--the devas or the asuras--and an unexpected answer comes from an unexpected place.